The Specifications and Ingredients Found in Commercially Available Toothpastes - Gundavarapu, Kalyan C; Ramachandra, Srinivas S; Dicksit, Daniel D; Gupta, Vivek V (Makara Journal of Health Research, 2017)
Background: The aim of this study was to evaluate the specifications and ingredients of various commercially available toothpastes in Malaysia. Methods: Various toothpaste brand samples were collected from malls & pharmacies in Petaling Jaya, Malaysia. Each brand was studied and information regarding the presence or absence of fluoride, the fluoride content, whether the fluoride content was displayed on the packaging, the type of fluoride present, and the country of manufacture was noted. Using this information, a comprehensive list of commercially available toothpastes in the Malaysian market was prepared. Results: the 57 toothpastes collected, 12.3% (n = 7) did not state their fluoride contents, 15.8% (n = 9) were non-fluoridated, and 72% (n = 41) were fluoridated. From the 41 fluoridated toothpastes, 80% specified the type of fluoride present, with 60% containing sodium monofluorophosphate and 40% containing sodium fluoride. Of the 41 fluoridated toothpastes, only 38% specified the parts per million of fluoride. Conclusions: There is lack of standardisation regarding the labelling specifications amongst various toothpastes on the Malaysian market. This standard needs to be identified and should include information regarding the type of fluoride, concentration of fluoride, country of manufacture, and other necessary specifications printed on the toothpaste packaging.